The liberal-republican quandary in Israel, Europe and the United States: early modern thought meets current affairs - Maissen, Thomas (Academic Studies Press, 2012)
Intro -- Table of Contents -- Introductory Remarks -- Republics, Revelations and Liberalisms: A Selective History of Early Modern Political Thought -- Political Hebraism, Past and Present -- The Polis in Seventeenth-Century Political Discourse: Athens Mirrored by Francis Rous, Marchamont Nedham, George Guillet de Saint-George and Jonathan Swift -- Were the Republics Able to Handle the Challenge? Commerce as a Driving Force Behind Changing Role Models in Eighteenth-Century Political Discourse -- Beyond the Republican Synthesis: Biblical Republicanism and the American Revolution -- Toleration, Liberty, and Rights: or, What Hobbes Knew, Others Feared, and Hohfeld Figured Out -- Old and New Justifications for War: Just Wars and Humanitarian Interventions -- Justice Over Charity: Some Dangers in Faith-Based Poverty Initiatives -- Has the Wheel Come Full Circle? Civic Service Debates in Israel -- Universal Jurisdiction, Really Serious Crimes, and the Liberal-Republican Debate -- Republican and Liberal Values in Coping With the Memory of World War II: The Swiss Holocaust Assets in a Transnational Perspective -- Europe and Israel Today: Can Their Incompatible "Never Again(s)" Be Reconciled? -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Geschichte 1600-2000; Republikanismus; Liberalismus; Politisches Denken; USA; Europa; Israel